Coccidioidomicose no estado de Ceará (1995-2007) : características clínico-laboratoriais e análise das frações protéicas do antígeno total de Coccidioides posadasii no imunodiagnóstico - Bandeira, Silviane Praciano (2008)
Coccidiodomycosis is a disease caused by dimorphic fungi of the Coccidioides genus – C. immitis and C. posadasii – which afflicts people and various animals, such as cattle, goats, rodents and dogs. It is restricted to the Americas and cases have been reported in the state of Ceará only since 1995. The infection generally results from inhaling the infectious structures arthroconidia -of the fungus. In its parasitic phase, the microorganisms responsible for the clinical signs of the disease have a spherical shape. Most cases are asymptomatic, and respiratory problems are the most common symptoms in patients that are clinically affected. The disease’s diagnosis is based on microbiological techniques such as direct examination of clinical specimens and culturing, but these procedures require specialized biosecurity level 3 facilities because the microorganism falls in biological class 3. The immunological approach appears promising because it does not require manipulation of the fungi and can be performed in various laboratories equipped for routine mycological tests. The aim of this work is to outline the clinical and laboratory profile of the cases of coccidiodomycosis that occurred in the state of Ceará between 1995 and 2007 and to report experiments to obtain antigenic fractions from fractioning Antígeno total of C. posadasii, as a possible means for immunodiagnosis of the disease. A total of 19 cases of the disease were cataloged in the study period. All the patients were young men with respiratory symptoms, except for one case. All but one of the patients reported they engaged in recreational hunting of armadillos. The laboratory approach in these cases consisted of microbiological examination combined with molecular, immunological, histopathological techniques or animal experiments. The protein fractioning of Antígeno total of C. posadasii produced three antigenic fractions with different protein content, electrophoretic profile and immunoreactivity according to the Western blotting technique. The 60-90% fraction showed an immunoreactive band of approximately 30 to 40 KDa, recognizable by sera from patients with coccidiodomycosis, but showed crossreactivity with some sera from patient with histoplasmosis. This protein band, in subsequent studies, can be characterized and purified for potential use as a tool for immunodiagnosis of the disease.